Introduction: Re-viewing the Past and Facing the Future. Issue 1 (1st March 2021) - Grove, Laurence; Magnussen, Anne; Miller, Ann
Abstract : This edition of European Comic Art begins by adopting a retrospective viewpoint and ends with a look to the future, not entirely rosy but not wholly bleak. Our first article offers a reassessment of the relationship between Hergé's Tintin and conservative Catholic discourses of the 1930s. We then move on to a personal recollection of a landmark moment in the legitimisation of comics in France: the Cerisy conference of 1987. In our third article, two virtuoso comics autobiographers reflect (in an email discussion that took place in 2006, here translated into English for the first time) on the loss of the searching, edgy tonality of early comics life writing in favour of something more crowd-pleasing. Finally, a young Brighton-based comics artist shares her love of the medium and her experience of solidarity among her fellow artists but has a cooler appraisal of the current political scene and the health of the comics culture in the United Kingdom.